STRUKTUR KOMUNITAS GASTROPODA PADA HAMPARAN LAMUN DI WILAYAH PESISIR NUSI DAN GERSEN, KABUPATEN NABIRE - Marce Souisa; Simon P. Leatemia; Selfanie Talakua (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
Gastropods plays an important role in the food chain on seagrass ecosystem and its existence are depend on the physical-chemical factors in the seagrass ecosystem. This study aims to determine the density and diversity of gastropods associated in seagrass habitat in Nusi and Gersen coastal waters. The measurement results of some physical-chemical waters variables, are still quite good for the life of gastropods. Species composition of gastropod in Nusi at higher than at the Gersen, but instead of individual density in Gersen more higher than Nusi. Diversity index of gastropods at Nusi station is higher (3,757) than Gersen (3.053), on the contrary the eveness and dominance index are higher at Gersen station than Nusi station. Community similarity index by species is low between the two stations, which indicates that the species of gastropods at both stations is quite different. The influence of human activity and higher utilizatin of gastropods in Nusi has lowered the density of gastropods in seagrass habitat, so it needs awareness efforts on the importance of gastropods and the seagrass habitat for coastal ecosystem.